Learning to learn: Towards a relational and transformational model of learning for improved integrated care delivery - Peter Tsasis; Jenna M. Evans; Linda Rush; John Diamond (Administrative Sciences, 2013)
Health and social care systems are implementing fundamental changes to organizational structures and work practices in an effort to achieve integrated care. While some integration initiatives have produced positive outcomes, many have not. We reframe the concept of integration as a learning process fueled by knowledge exchange across diverse professional and organizational communities. We thus focus on the cognitive and social dynamics of learning in complex adaptive systems, and on learning behaviours and conditions that foster collective learning and improved collaboration. We suggest that the capacity to learn how to learn shapes the extent to which diverse professional groups effectively exchange knowledge and self-organize for integrated care delivery.
Keywords: 350; integrated care; health services integration; complex adaptive systems; learning to learn; self-organization